Indicative variables of attrition: Application of Delphi Technique - Kumar M., Dileep; Govindarajo, Normala S (2013)
Case studies are one of the methodologies followed by researchers to arrive at observations where measurements are impossible, but deep rooted probing is possible. This case study analyzes the organizational and strategic planning problems that HAA & Associates, a small sized law firm, faces in coping with the competitive legal industry and business environment in Malaysia.The scenario posited in the case study has similarity with most other small law firms in Malaysia and the general business activities of other professional firms face and refer to various research sources that offer solutions.The goal is to provide a study of the organizational strategy and change management concepts.Some of the problems that the firm is facing include the role of the leader/owner, vision and mission, economic pressures, lack of understanding of marketing orientation, technological changes, regulation of the legal practices and training and development of the legal personnel.Although the legal profession is facing dramatic transformation, most law firms are not applying the required strategies necessary for adapting to the changing conditions. The research sources reviewed in the paper will be useful in identifying the suitable strategies necessary for ensuring success in the small legal firms and small professional firms.